Thermal energy storage and cooling load response - Lizhong Yang; Nastaran Barhemmati; Weihuan Zhao; Dongxu Ji; Srithar Rajoo; Alessandro Romagnoli (Asian Development Bank Institute (ADBI), 2024)
Thermal Energy Storage (TES) and Demand Response (DR) offer unique benefits to reducing the electricity consumption, carbon emission, investment, and operational cost of generating cooling energy by bridging the gap between cooling energy demand and production. To provide comprehensive guidance to policymakers, system planners, investors, clean energy advocates, and other relevant parties to accelerate the development of TES and DR technologies, this paper provides a comprehensive overview of the most common TES and DR strategies for cooling purposes, covering the working principles, advantages, development stages, technical limitations, suitable applications, and potential growth opportunities in the transition towards low carbon economy. The research directions and policy recommendations are also discussed for better TES and DR development and deployment, especially in Asia. Energy users and system planners can choose the most suitable TES and DR technology to reduce electricity consumption and carbon emissions for their energy systems, while policymakers, investors, and clean energy advocates can contribute to removing the economic, regulatory, or customer-related barriers to TES and DR deployment, which will jointly help fully release the enormous economic and environmental potential of TES and DR technologies.
Keywords: O3; O31; 330; thermal energy storage; demand response; phase change materials; low carbon; clean energy